Salusins, newly identified regulators of hemodynamics and mitogenesis, increase in polycystic ovarian syndrome - Celik, Onder; Yilmaz, Ercan; Celik, Nilufer; Minareci, Yagmur; Turkcuoglu, Ilgin; Simsek, Yavuz; Aydin, Suleyman (Taylor & Francis Ltd, 2013)
In the current study, we aimed to investigate whether serum salusin alpha and beta levels are different in PCOS subjects. Fifty women with PCOS and 50 healthy, age-and body mass index matched controls were included to the prospective cross-sectional study. All subjects underwent venous blood drawing on the early follicular phase after an overnight fasting. Serum salusin alpha and beta levels were measured with EIA, and ELISA respectively. The relationships between serum salusin levels and anthropometric and metabolic parameters were also assessed. Plasma salusin alpha and beta levels were higher in women with PCOS compared to control group. Serum salusin alpha level correlated positively with salusin beta and fasting serum insulin levels. The serum salusin beta levels were correlated positively with HOMA-IR, TG, LDL-C, LH, FSH, and total testosterone levels. Our results indicate that salusins, newly identified regulators of hemodynamics and mitogenesis, are increased within the serum of women with PCOS.
Keywords: Cardiovascular risk; insulin resistance; PCOS; salusin-alpha; salusin-beta